Analysis of Retail Investors’ Attitudes Toward IPO Investments - Arora, Amit Kumar; Kumar, Santosh; Kansal, Amit (Indian Journal of Finance, 2024)
Purpose : This research paper examined the investment behavior of retail investors in initial public offerings (IPOs) in India. IPOs served as an avenue for companies to raise capital by offering shares to the public for the first time. Retail investors, as crucial participants in the IPO market, played a significant role in shaping the overall investment landscape. The study aimed to analyze the factors influencing retail investors’ investment decisions and IPO investment outcomes. Methodology : The cross-sectional survey was carried out in April–July of 2023. A convenient sampling technique was applied. The data were analyzed using chi-square, regression analysis, t-test, and descriptive analysis. Findings : The study discovered that important considerations for selecting IPOs included goodwill, the company’s history, its present financial situation, management profile, promoter’s background, IPO grade, market participant disclosures, and the grey market premium. On the other hand, the promoter’s stake, IPO price band, current position in the secondary market, and competitive position were not found to be significant factors. The study also found that fear of loss of money, lack of proper knowledge, and the fact that family does not allow are the reasons for not investing in the IPOs. Practical Implications : The results clarified the primary factors influencing the behavior of retail investors in IPOs and offered valuable perspectives on how to improve investor protection and market efficiency through regulatory interventions and effective investor education. Originality : This study was different from previous IPO studies in that it concentrated on retail investors. When it comes to comprehending the distinct attitudes, perspectives, and decision-making processes of retail investors in IPOs, there is a clear vacuum in the literature. The present study also analyzed those respondents who were not willing to invest in IPOs to determine the reason for the same.